Determinants of Employee Happiness in an Information Technology Company in India - T, Thiruvenkadam; Jayasingh, Sudarasan (International Journal of Engineering and Technology, 2018)
Happiness is the experience of pleasure, satisfaction, or affirmative well-being, pooled with a sense that oneâ€™s life is good, significant, and valuable. Happiness is a rational or emotional condition of comfort defined by optimistic or enjoyable emotions ranging from satisfaction to intense delight. The study had been carried out with the objectives to study the level of happiness of employees, to find out the determinants of employee happiness, to analyse the influence of demographic factors on employee happiness and to test how employee happiness is correlated with various factors like, attitude towards self, attitude towards job, career growth and development, organization culture and alignment, physical and mental well-being, work life balance, relationship with team, relationship with managers. The research is descriptive in nature. The size of the population for the IT vertical of the organization with associates in the experience range of 4-7 years is 6000 and the sample taken for study is 410 employees. Purposive sampling method was used for selecting samples from the population. The samples are chosen across different projects in the organization and a quota is assigned in each project for selecting the sample. The data analysis has been done using correlation, chi-square, one way ANOVA and Regression analysis. The results of the study could establish a moderate positive co-relation between the happiness and all eight constructs. The study had been concluded with a remark that the constructs like work life balance, physical and mental well-being, relationship with managers has a significant influence on employee happiness.Â Â Â